These equations are called transposition. Essentially what you’re going to do is re-arrange the formula to get the value of the unknown variable (the letter) that you want. This is probably worth YouTubing however I’ll do 17) for you in the hopes that it may jog your memory.
-6(1-5x)=54. The first step we should do here is expand the brackets (Multiply the outside by the inside)
-6+30x=54. We don’t know the value of x therefore we cannot add the values of x and the known numbers together.
30x=54+6. In this step we move the -6 to the other side of the equation. Therefore 54+6 = 60
30x=60. We now know that 30x=60, therefore to get the value of X on it’s own, we divide the sum by 30.
X=2. As you can see, the result is that in this equation, our unknown variable is equal to 2.
Please let me know if there is anything in particular which you do not understand about this, as I am going off of the assumption that you have been taught transposition and algebra before.
Hope this helps :)